Climate change adaptation in developed nations from theory to practice - Ford, James D.; Berrang-Ford, Lea; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
It is now widely accepted that adaptation will be necessary if we are to manage the risks posed by climate change. What we know about adaptation, however, is limited. While there is a well established body of scholarship proposing assessment approaches and explaining concepts, few studies have examined if and how adaptation is taking place at a national or regional level. This deficit in understanding is particularly pronounced in developed nations which have typically been assumed to have a low vulnerability to climate change. Yet as recent research highlights, this assumption is misplaced: developed nations are experiencing the most pronounced changes in climatic conditions globally and have significant pockets of vulnerability. Chapters in this book profile cases from different sectors in developed nations where specific adaptation measures have been identified, implemented, and evaluated. The contributions provide practical advice and guidance that can help guide adaptation planning in multiple contexts, identifying transferable lessons. It is a comprehensive and timely piece of work on an emerging body of literature that is critical for both academics and policy makers to be aware of and learn from in regards to the importance of adaptation and adaptation needs associated with climate change and variability.  It is a strong step forward in bringing together this literature and thinking in one collective piece of writing. Chris Furgal, Trent University, Canada Lead Author IPCC 4th Assessment Report   This volume is ambitious in scope and distinctive in focus. It is not about climate change science or mitigation or impacts... but focuses clearly on the processes of adaptation. This volume represents a valuable compilation of ideas, methods and applications dealing with adaptation to climate change in developed nations. Barry Smit, University of Guelph, Canada Canada Research Chair in Global Environmental Change   This book provides key insights from leading scholars who are addressing an important but neglected question: How easy is it to adapt to climate change in practice? Focusing on evidence from developed countries, the contributions provide reasons for both optimism and concern, and lessons that are critical for anyone interested in climate change policy and a sustainable future. Karen O'Brien, University of Oslo, Norway Chair of Global Environmental Change and Human Securit
Section I: Introduction and Overview -- Section II: Adaptation in the Public Health Sector -- Section III: Adaptation in the Industrial Sector -- Section IV: Adaptation in the Urban Environment -- Section V: Adaptation in the Agricultural Sector -- Section VI: Adaptation in Rural and Resource-dependent Communities.-  Section VII: Future Directions -- Index.
Electronic reproduction.
Keywords: Climatic changes -- Developed countries; Public health -- Environmental aspects -- Developed countries; Industries -- Environmental aspects -- Developed countries; Metropolitan areas -- Environmental aspects -- Developed countries; Agriculture -- Environmental aspects -- Developed countries; Electronic books